Strong Slavic and Iberian Identity Syndrome in the Perspectives of Glocalization - Miczka, Tadeusz (European Scientific Journal, ESJ, 2017)
My assumption is that, although those identities which are weak, antiessential, mobile and easily â€œopenâ€ to new phenomena are particularly popular in postmodern epoch, in Iberian and Slavic cultures strong identities, which are essential, stable and coherent, play an important role in social life. It is caused mainly by such factors as adherence of the cultures to the difficult past (inheritance, tradition and memory), producing of rich repertory of their own language systems and symbolic signs of another type and devotion to values, which maintain the sense of separateness or even uniqueness. I analyze the most important tensions which exist nowadays between those strong and weak cultural identities as a result of integrative and globalization processes, which are reinforced by the expansion of the media. The focus of my reasoning is, as the most current interpreting perspective, the phenomenon of glocalization, which is understood as globalization (globalizm, globality) strongly connected with localization (localism, locality). I consider how in social practice tensions between cultural identities are used â€œto openâ€ locally to globalization and simultaneously participate in global processes which â€œopenâ€ to locality? The main concern then, is to produce new rules of intercultural communication.